Comprehensive Understanding and Controlling the Defect Structures: An Effective Approach for Organic-Inorganic Hybrid Perovskite-Based Solar-Cell Application - Lee, Young Mi; Maeng, Inhee; Park, Jinwoo; Song, Myungkwan; Yun, Jung-Ho; Jung, Min-Cherl; Nakamura, Masakazu (Frontiers in Energy Research, 2018)
Understanding the defect structure in organic-inorganic hybrid perovskite material (OHP) is a crucial role to explain several physical properties such as material stability, energy band, carrier mobility, and so on. In the solar-cell applications using OHP, finding, understanding, and controlling defects is essential to making a more advanced device with high efficiency and stability. Naturally, we need to find, understand, and control the possible defects in OHP. However, the defect research field in OHP material is just beginning now. In this short review, we will explore the kinds of defects and their effects on OHP.